2001
DOI: 10.1002/ps.407
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between sulfonylurea herbicide treatment of host plants and the performance of herbivorous insects

Abstract: Previous work had shown that the sulfonylurea herbicide chlorsulfuron affected the survival of a herbivorous insect species dwelling on a sub-lethally exposed host plant. Further experiments have been conducted to establish whether this negative effect was a single occurrence characteristics for the specific insect-plant interaction and the specific herbicide tested. Three insect-plant interactions were tested for the effects of selected sulfonylurea herbicides, i.e. metsulfuron-methyl, chlorsulfuron and tribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…Evaluations of herbicide effects on butterflies and other insects are generally only for species of agricultural importance, such as pollinators, decomposers, and predators (e.g., Ahn et al 2001;Haughton et al 2001a,b). These effects vary depending on site-specific (Haughton et al 2001a,b;Stark and Banks 2003) and species-specific variables (Kjaer and Heimbach 2001;Stark and Banks 2003) and on the herbicide used (Agnello et al 1986a). Although some herbicides have no effect on certain insect species (Agnello et al 1986b;Kjaer and Heimbach 2001), others may be toxic, leading to decreased survival, altered development time, or reduced size of the insect species (Brown 1987;Ahn et al 2001;Russell and Schultz 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluations of herbicide effects on butterflies and other insects are generally only for species of agricultural importance, such as pollinators, decomposers, and predators (e.g., Ahn et al 2001;Haughton et al 2001a,b). These effects vary depending on site-specific (Haughton et al 2001a,b;Stark and Banks 2003) and species-specific variables (Kjaer and Heimbach 2001;Stark and Banks 2003) and on the herbicide used (Agnello et al 1986a). Although some herbicides have no effect on certain insect species (Agnello et al 1986b;Kjaer and Heimbach 2001), others may be toxic, leading to decreased survival, altered development time, or reduced size of the insect species (Brown 1987;Ahn et al 2001;Russell and Schultz 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These effects vary depending on site-specific (Haughton et al 2001a,b;Stark and Banks 2003) and species-specific variables (Kjaer and Heimbach 2001;Stark and Banks 2003) and on the herbicide used (Agnello et al 1986a). Although some herbicides have no effect on certain insect species (Agnello et al 1986b;Kjaer and Heimbach 2001), others may be toxic, leading to decreased survival, altered development time, or reduced size of the insect species (Brown 1987;Ahn et al 2001;Russell and Schultz 2010). They can also have an indirect effect on insect population abundance by creating an unsuitable habitat, such as the loss or avoidance of nectar and food plants (Feber et al 1996;Pratt et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Developmental duration and fecundity of the insects were measured to determine whether the herbivorous insects had a good “biological fit” on a particular host plant or not. A short developmental duration and high fecundity may optimize a more suitable environment for the insects 25 . When B. macroscopa was reared on I. aquatica , the total duration of the egg and larval stages were the shortest, but the survival rates in the larval stage, and the adult fecundity were the highest, suggesting that I. aquatica may be the most suitable host for B. macroscopa .…”
Section: Discussionmentioning
confidence: 99%
“…There has been few investigations focusing on the interaction between plants and insects under the application of other herbicides such as atrazine or other kinds of sulfonylurea herbicides (Dewey, 1986; Kjaer and Heimbach, 2001). In the study of atrazine in 1986, the researchers focused on the community of the insects and suggested that herbicides affected the community of the insects community indirectly by reducing the food and habitat (Dewey, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of atrazine in 1986, the researchers focused on the community of the insects and suggested that herbicides affected the community of the insects community indirectly by reducing the food and habitat (Dewey, 1986). In the study of sulfonylurea herbicide application on different host plants which were not sensitive, the activity of insects feeding on them were not severely affected except the death rate of Gastrophysa polygoni larvae (Kjaer and Heimbach, 2001). In our investigation, first of all, tobaccos are sensitive to BSM residues and show remarkable symptoms.…”
Section: Discussionmentioning
confidence: 99%